2016
DOI: 10.1016/j.cmet.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Pro-inflammatory Macrophages Cause Insulin Resistance in an Intestinal Ccl2/Ccr2-Dependent Manner

Abstract: High-fat diet (HFD) induces low-grade chronic inflammation and insulin resistance. However, little is known about the mechanism underlying HFD-induced chronic inflammation in peripheral insulin-responsive tissues. Here, we show that colonic pro-inflammatory macrophages regulate insulin sensitivity under HFD conditions. To investigate the pathophysiological role of colonic macrophages, we generated macrophage-specific chemokine (C-C Motif) receptor 2 (Ccr2) knockout (M-Ccr2KO) and intestinal epithelial cell-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(166 citation statements)
references
References 57 publications
7
158
1
Order By: Relevance
“…Tnfa expression did not increase in mice at 4 or 10 weeks of a HFD (Supplemental Figure 5D). These findings are consistent with previous reports showing that mice develop adipose and systemic insulin resistance within several days to 4 weeks of a HFD (44,45), whereas the number of M1 macrophages in WAT increases only within 8 to 10 weeks of a HFD (10,15,45,46). The finding that HFD-induced insulin resistance precedes the accumulation of M1 macrophages is consistent with our above conclusion that insulin resistance leads to inflammation.…”
Section: Resultssupporting
confidence: 83%
“…Tnfa expression did not increase in mice at 4 or 10 weeks of a HFD (Supplemental Figure 5D). These findings are consistent with previous reports showing that mice develop adipose and systemic insulin resistance within several days to 4 weeks of a HFD (44,45), whereas the number of M1 macrophages in WAT increases only within 8 to 10 weeks of a HFD (10,15,45,46). The finding that HFD-induced insulin resistance precedes the accumulation of M1 macrophages is consistent with our above conclusion that insulin resistance leads to inflammation.…”
Section: Resultssupporting
confidence: 83%
“…These effects were mediated by early induction of CCL2 in intestinal epithelial cells, which attracted pro-inflammatory macrophages to colon tissue [9]. In this study, although we observed significantly greater colon CCL2 mRNA expression with milk SM intake, we did not observe any significant changes between groups in gene expression of gut barrier markers or macrophage infiltration/inflammation in colon and mesenteric adipose tissues.…”
Section: Discussioncontrasting
confidence: 50%
“…Recently, chronic feeding of HFD to mice was shown to increase colonic pro-inflammatory macrophages and gut inflammation, which promoted LPS translocation, insulin resistance, and adipose tissue inflammation [9]. These effects were mediated by early induction of CCL2 in intestinal epithelial cells, which attracted pro-inflammatory macrophages to colon tissue [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38) Since macrophages are representative cells expressing P2X7R highly, [9][10][11][12] and Kurashima et al, demonstrated that mast cells treated with ATP showed the expression of chemokines such as Ccl2, 16) it is suggested that administration of magnesium might inhibit the development of high-fat diet-induced insulin resistance, leading to prevention of onset of lifestyle-related type II diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%